2020
DOI: 10.1007/s00167-020-05906-9
|View full text |Cite
|
Sign up to set email alerts
|

Trochleoplasty improves knee flexion angles and quadriceps function during gait only if performed bilaterally

Abstract: Purpose To investigate if a trochleoplasty increases knee flexion angles and extensor moments in the gait of patients with patellar instability and to compare postoperative gait to a healthy control group. Methods A bilateral dislocation group (6 patients) and a unilateral dislocation group (14 patients) were treated with bilateral and unilateral trochleoplasty, respectively. Kinematics and kinetics of the lower extremity were captured using 3D‐gait analysis (VICON, 12 cameras, 200 Hz, plug‐in‐gait, two force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Almost all the studies [ 24 , 25 , 26 , 28 , 29 , 34 ] achieved a total score of 18 or higher out of a possible total of 22 points for the STROBE checklist. There is only one study by Sowiński et al [ 27 ] where nine of the 22 recommended points of the STROBE checklists were missing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost all the studies [ 24 , 25 , 26 , 28 , 29 , 34 ] achieved a total score of 18 or higher out of a possible total of 22 points for the STROBE checklist. There is only one study by Sowiński et al [ 27 ] where nine of the 22 recommended points of the STROBE checklists were missing.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies failed to report the specific demographic information of their participants [ 25 , 27 ]. Only two studies [ 28 , 34 ] reported how they derived their sample size. The results of the critical appraisal for each article are displayed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations